2018
DOI: 10.3389/fimmu.2018.02380
|View full text |Cite
|
Sign up to set email alerts
|

CAR T Cell Therapy for Neuroblastoma

Abstract: Patients with high risk neuroblastoma have a poor prognosis and survivors are often left with debilitating long term sequelae from treatment. Even after integration of anti-GD2 monoclonal antibody therapy into standard, upftont protocols, 5-year overall survival rates are only about 50%. The success of anti-GD2 therapy has proven that immunotherapy can be effective in neuroblastoma. Adoptive transfer of chimeric antigen receptor (CAR) T cells has the potential to build on this success. In early phase clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 192 publications
(211 reference statements)
0
113
0
1
Order By: Relevance
“…66 For example, CAR-T cells targeting GD2 are being explored in the clinic for treatment of NB. 67 Additionally, like PD-L1, our TCGA analysis revealed several other immunosuppressive factors (eg, CTLA-4, TGF-β, IL-10) that are correlated with high STING expression in human NB ( figure 1A) and may therefore also be promising targets in the design of combination regimens leveraging STING agonists. Similarly, STING-NPs may synergize with approved treatments for NB (eg, chemotherapy, radiation therapy, anti-GD2 therapy) by generating an immunosupportive context for antigen cross-presentation and T cell priming of locally liberated tumor antigen.…”
Section: Open Accessmentioning
confidence: 88%
“…66 For example, CAR-T cells targeting GD2 are being explored in the clinic for treatment of NB. 67 Additionally, like PD-L1, our TCGA analysis revealed several other immunosuppressive factors (eg, CTLA-4, TGF-β, IL-10) that are correlated with high STING expression in human NB ( figure 1A) and may therefore also be promising targets in the design of combination regimens leveraging STING agonists. Similarly, STING-NPs may synergize with approved treatments for NB (eg, chemotherapy, radiation therapy, anti-GD2 therapy) by generating an immunosupportive context for antigen cross-presentation and T cell priming of locally liberated tumor antigen.…”
Section: Open Accessmentioning
confidence: 88%
“…In fact, several therapeutic antibodies targeting GD2 were developed, and later the mAb Dinutuximab was approved for patients with high-risk neuroblastoma 3 . Moreover, targeting GD2 with CAR T cells has shown some efficiency in early clinical studies 51 . We have demonstrated previously the efficiency of targeting GD2 with UniCAR T cells 38 .…”
Section: Discussionmentioning
confidence: 99%
“…There are currently many open clinical trials of CAR-T therapy for patients with relapse or progression neuroblastoma. 16 Our data showed that CAR-T therapy was well tolerated; it provided a short-term therapeutic effect for patients with refractory and recurrent neuroblastoma. However, it did not improve the long-term survival rate.…”
Section: Treatment For Neuroblastoma Includes Chemotherapy S U Rg Ementioning
confidence: 61%